Las estrategias metodológicas y su relación en el aprendizaje de los niños y niñas de primer grado de educación general básica de la unidad educativa “Dr. Gonzalo Abad Grijalva” de la ciudad de Piñas, provincia de El Oro, periodo 2014-2015. Lineamientos propositivos - Romero Freire, Pahola del Rocío (2014)
The titled thesisTHE METHODOLOGICAL STRATEGIES AND THEIR RELATIONSHIP WITH BASIC GENERALEDUCATION FIRST GRADE CHILDREN LEARNING "Dr. GONZALO ABAD GRIJALVA"SCHOOL, PIÑAS CITY, EL ORO PROVINCE, PERIOD 2014-2015. PROPOSITIONAL GUIDELINES. It was conducted according to the Provisions the Regulation of Academic Board ofLoja National University. The general objective that guided this investigation was:ToAnalyzing Methodological Strategies and their relationship with basicgeneral education first gradechildren Learning "Dr. Gonzalo Abad Grijalva" school, Piñas city, el Oro Province, period 2014-2015 The used methods were: Scientific, Inductive, Deductive, Analytic-synthetic and Statistical Model. The techniques were the following ones: The Survey applied the teacher s of High school, First Grade of Basic General Education of the School "Dr. Gonzalo Abad Grijalva" to knowthe methodological strategies used in their daily work; and the Guide of Observation applied the children and girls of First Grade of Basic General Education of the School "Dr. Gonzalo Abad Grijalva" to determine the Learning From the survey results it is concluded that: 100% of the teachers surveyed if Methodological Strategies used in their daily work Of the application of the Guide of Observation it was determined that: 66% of the children assessed respondents Very Satisfactory, Satisfactory 24%; and 10% Unsatisfactory